Evaluation of Amino Nitriles and an Amino Imidate as Organocatalysts in Aldol Reactions - Vagkidis, Nikolaos; Brown, Alexander J.; Clarke, Paul A. (Synthesis, 2019)
The efficiency of l-valine and l-proline nitriles and a tert-butyl l-proline imidate as organocatalysts for the aldol reaction have been evaluated. l-Valine nitrile was found to be a syn-selective catalyst, while l-proline nitrile was found to be anti-selective, and gave products in modest to good enantioselectivities. tert-Butyl l-proline imidate was found to be a very efficient catalyst in terms of conversion of starting reagents to products, and gave good anti-selectivity. The enantioselectivity of the tert-butyl l-proline imidate was found to be good to excellent, with products being formed in up to 94% enantiomeric excess.
Keywords: asymmetric synthesis; organocatalysis; aldol reaction; amino nitrile; amino imidate